Electrochemical immunosensor for the detection of aflatoxin B1 in palm kernel cake and feed samples - Azri, Farah Asilah; Selamat, Jinap; Sukor, Rashidah (Multidisciplinary Digital Publishing Institute, 2017)
Palm kernel cake (PKC) is the solid residue following oil extraction of palm kernels and useful to fatten animals either as a single feed with only minerals and vitamins supplementation, or mixed with other feedstuffs such as corn kernels or soy beans. The occurrence of mycotoxins (aflatoxins, ochratoxins, zearalenone, and fumonisins) in feed samples affects the animal’s health and also serves as a secondary contamination to humans via consumption of eggs, milk and meats. Of these, aflatoxin B1 (AFB1) is the most toxically potent and a confirmed carcinogen to both humans and animals. Methods such as High Performance Liquid Chromatography (HPLC) and Liquid Chromatography–Mass Spectrometry (LC-MS/MS) are common in the determination of mycotoxins. However, these methods usually require sample pre-treatment, extensive cleanup and skilled operator. Therefore, in the present work, a rapid method of electrochemical immunosensor for the detection of AFB1 was developed based on an indirect competitive enzyme-linked immunosorbent assay (ELISA). Multi-walled carbon nanotubes (MWCNT) and chitosan (CS) were used as the electrode modifier for signal enhancement. N-ethyl-N′-(3-dimethylaminopropyl)-carbodiimide (EDC) and N-hydroxysuccinimide (NHS) activated the carboxyl groups at the surface of nanocomposite for the attachment of AFB1-BSA antigen by covalent bonding. An indirect competitive reaction occurred between AFB1-BSA and free AFB1 for the binding site of a fixed amount of anti-AFB1 antibody. A catalytic signal based on horseradish peroxidase (HRP) in the presence of hydrogen peroxide (H2O2) and 3,3′,5,5′-tetramethylbenzidine (TMB) mediator was observed as a result of attachment of the secondary antibody to the immunoassay system. As a result, the reduction peak of TMB(Ox) was measured by using differential pulse voltammetry (DPV) analysis. Based on the results, the electrochemical surface area was increased from 0.396 cm2 to 1.298 cm2 due to the electrode modification with MWCNT/CS. At the optimal conditions, the working range of the electrochemical immunosensor was from 0.0001 to 10 ng/mL with limit of detection of 0.1 pg/mL. Good recoveries were obtained for the detection of spiked feed samples (PKC, corn kernels, soy beans). The developed method could be used for the screening of AFB1 in real samples.